Influences of Teacher–Child Relationships and Classroom Social Management on Child-Perceived Peer Social Experiences During Early School Years - Chen, Jing; Jiang, Hui; Justice, Laura M.; Lin, Tzu-Jung; Purtell, Kelly M.; Ansari, Arya (Frontiers in Psychology, 2020)
Interactions with teachers and peers are critical for children’s social, behavioral, and academic development in the classroom context. However, these two types of interpersonal interactions in the classroom are usually pursued via separate lines of inquiries. The current study bridges these two areas of research to examine the way in which teachers influence child-perceived peer social support and peer victimization for 2,678 children within 183 classrooms in preschool through grade three. Two levels of teacher influence are considered, namely teacher-child closeness and conflict relationships at the child-level, and teacher management of interpersonal interactions at the classroom-level. Results of multilevel regression models showed that teacher-child closeness was associated with the growth of child-perceived peer social support from fall to spring, whereas teacher-child conflict and teachers’ behavior management practices were associated with the change in child-perceived peer victimization across the academic year. These associations were unique and above and beyond the influence of children’s actual peer social interactions, including reciprocal friendships and the collective classroom reputation of peer victimization. Collectively, findings highlight the multi-faceted teacher roles in shaping children’s perceptions of their peer social experiences during the earliest years of schooling.